Waste Level Monitoring System Based on IoT (Internet of Things) Using LoRa (Long-Range) Technology - Rinto Hadi; Agus Wibowo; Dana Indra Sensue (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2026)
The increasing need for efficient waste management encourages the development of monitoring systems that can provide timely information on the condition of waste bins. This study proposes an Internet of Things (IoT)-based waste level monitoring prototype that employs LoRa communication for wireless data transmission. The system was developed using Arduino Uno, Arduino Mega, LoRa modules, Raspberry Pi, and an ultrasonic sensor to detect the waste level and transmit the collected data to a monitoring dashboard. A quantitative experimental method was applied, supported by Quality of Service (QoS) analysis, to evaluate LoRa network performance. The testing was conducted in a non-line-of-sight (NLOS) environment using a 433 MHz LoRa frequency. The experiment involved 30 testing scenarios, consisting of five transmission distances, namely 20 m, 40 m, 60 m, 80 m, and 100 m, combined with six spreading factor settings from SF7 to SF12. The evaluation focused on packet loss, throughput, and time on air. The results indicate that transmission performance was influenced by environmental obstruction and spreading factor configuration. Packet loss was mainly observed at 80 m, with the highest loss reaching 9% at SF7, while higher spreading factor values tended to reduce packet loss. In terms of throughput, increasing the spreading factor decreased the transmission rate, whereas the time on air became longer. These findings show that LoRa communication can be implemented for waste bin level monitoring, although signal barriers in NLOS conditions may affect data transmission quality.